A NOTE ON WEAKLY PRIME HYPERIDEALS AND (1, n) HYPERIDEALS ON MULTIPLICATIVE HYPERRINGS - Ay, Elif Ozel; Yesilot, Gursel (VINCA INST NUCLEAR SCI, 2022)
In this article we give the definition of weakly prime hyperideals over multiplicative hyperring. We provide important results showing the relations between prime hyperideals and weakly prime hyperideals. Then we give definition of weakly n-hyperideal and weakly (1, n) hyperideal over multiplicative hyperrings. Then we investigate of their properties and give some examples. Hyperstructures are very important topic because it satisfy to study multidisiplinary. Especially in chemistry, coding theory, geometry, artificial intelligence, etc.
Keywords: multiplicative hyperrings; n-hyperideal; (1, n) hyperideal; weakly hyperideal; IDEALS; Thermodynamics